The Influence of Ruggedness Reviews 3-Dimensional Photo Carving Media Based on 3-Axis CNC Router - Setyaningsih, Noor Yulita Dwi; Annudin, Khan; Solekhan, Solekhan (Journal of Robotics and Control (JRC), 2021)
Today's face relief is very popular with people, both for gifts at special events or for mementos. Not everyone is able and able to produce or create relief carving 3-dimensional photos properly, so research on 3D photo carving using a CNC machine was made. CNC machine is a tool used to engrave and produce 3-dimensional photo engraving automatically. This research uses the Aspire application to create a G-Code type image. Next, connect the Arduino which in this case is used as the control device to enter the G-code obtained using the GRBL Control application. The gap in media reviews affects the time it takes in the manufacturing process, wherewith the same image design it is found that the greater the stretch of the reviews, the faster the time needed but the carving results are lined and rough. Likewise, the opposite condition, the smaller the gap in the review, the longer it takes, and the results obtained are smoother. So that in the future it can make a combination of choices from the stretch of reviews for engraved images.